Fabrication and experimental characterization of nanochannels - Phan, Vinh-Nguyen (2012)
Nanofluidics is the science and technology involving a fluid flowing in or around structures with a least one dimension in the nanoscale, which is defined as the range from 1 nm to 100 nm. In this paper, we present the fabrication and characterization of nanochannels in silicon and glass. Since the lateral dimension of the channels is limited by the wavelength of UV light used in photolithography, the channel width can only be fabricated in the micrometer scale. However, the depth of the channel can be controlled precisely by etch rate of reactive ion etching (RIE). Microchannels and access holes were etched with deep reactive ion etching (DRIE). Both nanonochannel and microchannel were sealed by a Pyrex glass wafer using anodic bonding. The fabricated nanochannels were characterized by capillary filling and evaporation experiments. Due to the small channel height and weak fluorescent signal, fluorescent techniques are not suitable for the characterization of the nanochannels. A long exposure time due to the limited amount of fluorescent molecules inhibit the measurement of transient and dynamic processes. However, as the channel height shorter than all visible wavelengths, the contrast in refractive indices of air and liquid allow clear visualization of nanochannels filled with liquids. Automatic image processing with MATLAB allows the evaluation of capillary filling in nanochannels. Interesting phenomena and discrepancies with conventional theories are presented.